Women's Issues and Their Fates in the US Congress. Issue 4 (8th July 2016) - Volden, Craig; Wiseman, Alan E.; Wittmer, Dana E.
Abstract : Significant scholarship indicates that female legislators focus their attention on "women's issues" to a greater extent than do male lawmakers. Drawing on over 40 years of bill sponsorship data from the US House of Representatives, we define women's issues in terms of those sponsored at a greater rate by women in Congress. Our analysis reveals that most (but not all) of the classically considered women's issues are indeed raised at an enhanced rate by congresswomen. We then track the fate of those issues. While 4 percent of all bills become law, that rate drops to 2 percent for women's issues and to only 1 percent for women's issue bills sponsored by women themselves. This pattern persists over time—from the early 1970s through today—and upon controlling for other factors that influence bills success rates. We link the bias against women's issues to the committee process, and suggest several avenues for further research.